Teachers' emotional exhaustion during the COVID-19 pandemic: Levels, changes, and relations to pandemic-specific demands. (January 2023) - Klusmann, Uta; Aldrup, Karen; Roloff-Bruchmann, Janina; Carstensen, Bastian; Wartenberg, Gyde; Hansen, Julia; Hanewinkel, Reiner
Abstract: We aimed to identify the levels of and changes in emotional exhaustion experienced by teachers and principals during the COVID-19 pandemic and pandemic-related stressors and resources. In a German sample of 2157 teachers and 374 principals, we found high levels and an increase of emotional exhaustion. Results from multi-group structural equation modeling analyses indicated that health concerns and workload were positively and social support negatively related to emotional exhaustion. Additional analyses of an open response question confirmed that teachers and principals experienced their work during the COVID-19 pandemic as predominantly stressful. These results indicate the importance of supporting both teachers and principals in reducing their exhaustion to help students overcome the consequences of the COVID-19 pandemic.